Optical glass and optical element

The optical glass composition with specific component ratios addresses the challenge of meeting modern safety standards and precision molding requirements by achieving high refractive index, low dispersion, and chemical durability, suitable for automotive applications.

JP2025006469APending Publication Date: 2025-01-17OHARA INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023107282
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing optical glasses do not meet modern safety standards for automobiles and are not suitable for precision molding due to insufficient chemical durability and optical properties.

Method used

Optical glass composition with specific ratios of components such as Li2O, ZnO, SiO2, Al2O3, and B2O3, adjusted to achieve high refractive index, low dispersion, and high chemical durability, enabling precision molding.

Benefits of technology

The glass exhibits high refractive index and low dispersion, with excellent chemical durability, allowing for precision molding and meeting strict safety standards for automotive applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025006469000001_ABST
    Figure 2025006469000001_ABST
Patent Text Reader

Abstract

To provide an optical glass that has optical constants of high refractive index and low dispersion, while offering high chemical durability, and enabling precise mold forming.SOLUTION: An optical glass is characterized by, in mass% based on oxides, the total content of components (Li2O+ZnO) being 6.0% or more, the mass ratio of the content of components (Al2O3 / B2O3) being more than 0 and 2.5 or less, SiO2 / B2O3 being 0.6 or more, (SiO2+Al2O3) / B2O3 being 0.8 or more and a refractive index (nd) being and 1.65000 or more and 1.75000 or less, wherein the optical glass exhibits an acid resistance grade (RA) of class 3 or higher under the powder method.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical glass and an optical element. [Background technology]

[0002] Optical glass and optical elements can be used to improve the optical properties of cameras and imaging devices by combining lenses with different optical regions, or to be installed in optical devices to realize various optical designs. In recent years, the market for optical devices for automobiles has been expanding with the increasing demand for driving records and autonomous driving technology.

[0003] In particular, for optical devices mounted on automobiles, there is a high demand for optical glass with a high refractive index and low dispersion, as the optical devices themselves need to be made smaller and lighter, and images need to be acquired over a wide range. This optical glass is required to have high chemical durability, as strict safety standards are applied to automobiles.

[0004] In addition, because optical devices mounted on automobiles require low-cost mass production, it is necessary to manufacture spherical and aspherical lenses by a precision molding method in which a preform material made by cutting and polishing a gob or glass block is heated and softened, and then pressure-molded in a mold with high-precision surfaces, rather than by manufacturing lenses by grinding or polishing, thereby eliminating the grinding and polishing steps and enabling low-cost mass production.To make it possible to manufacture lenses by such precision molding methods, optical glass is required to have a low glass transition point. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2007-137701 A [Patent Document 2] WO2018 / 003720 publication Summary of the Invention [Problem to be solved by the invention]

[0006] For example, Patent Document 1 discloses optical glass that has a refractive index (nd) of 1.65 to 1.75, an Abbe number (νd) of 45 or more, and has high weather resistance and is suitable for precision molding. However, it is difficult to say that the glass described in Patent Document 1 satisfies today's strict safety standards.

[0007] Furthermore, Patent Document 2 discloses optical glass that has desired optical properties, good chemical durability, and can meet today's strict safety standards, but it is difficult to say that this glass is applicable to precision molding.

[0008] The present invention has been made in view of the above problems, and an object of the present invention is to provide an optical glass and an optical element which have optical constants of high refractive index and low dispersion, while also having high chemical durability and which can be precision molded. [Means for solving the problem]

[0009] The present inventors have conducted extensive testing and research in order to solve the above-mentioned problems, and as a result have found that for a glass containing a certain amount of the sum of the components (Li2O+ZnO) and also containing SiO2 and Al2O3 components, the amount of weight loss caused by acid can be predicted from the mass ratio Al2O3 / B2O3. They have also found that by adjusting SiO2 / B2O3 and (SiO2+Al2O3) / B2O3 accordingly, it is possible to obtain optical glass and optical elements which have optical constants of high refractive index and low dispersion, while also having high chemical durability and which are suitable for precision molding. Specifically, the present invention provides the following:

[0010] (1) Mass percent based on oxides: The sum of the component contents (Li2O+ZnO) is 6.0% or more The mass ratio of the content of the components, Al2O3 / B2O3, is more than 0 and is 2.5 or less, SiO2 / B2O3 is 0.6 or more, (SiO2+Al2O3) / B2O3 is 0.8 or more, Refractive index (n d ) Optical glass with a powder method acid resistance rating (RA) of 3 or higher.

[0011] (2) The optical glass according to (1), in which the mass ratio of the contents of the components, Al2O3 / B2O3, is 1.5 or less.

[0012] (3) Abbe number (ν d ) is 45 or more, and the glass transition point (Tg) is 560° C. or less.

[0013] (4) An optical glass according to any one of (1) to (3), in which the ratio of the contents of the components Al2O3 / B2O3 is such that the powder method acid resistance evaluation result is 0.65>-0.5411×(Al2O3 / B2O3)+0.7383.

[0014] (5) The optical glass according to any one of (1) to (4), in which the sum of the contents of the components (SiO2 + Al2O3) is 18 or more.

[0015] (6) An optical element made of the optical glass according to (5). Effect of the Invention

[0016] According to the present invention, it is possible to provide an optical glass and an optical element which have optical constants of high refractive index and low dispersion, high chemical durability, and which can be precision molded. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a graph showing the relationship between the ratio of the content of components, Al2O3 / B2O3, and the weight loss rate (mass%) of a glass sample for the glasses of the examples of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, the embodiments of the optical glass of the present invention will be described in detail. The present invention is not limited to the following embodiments, and can be practiced with appropriate modifications within the scope of the object of the present invention. Note that, although explanations of duplicated parts may be omitted as appropriate, this does not limit the gist of the invention.

[0019] [Glass components] The composition range of each component constituting the optical glass of the present invention is described below. Unless otherwise specified in this specification, the content of each component is expressed as mass% relative to the total mass of the composition converted into oxide. Here, "composition converted into oxide" refers to a composition that expresses each component contained in the glass, assuming that oxides, composite salts, metal fluorides, etc. used as raw materials for the glass components of the present invention are all decomposed and converted into oxides during melting, with the total mass number of the generated oxides being 100 mass%.

[0020] The SiO2 component is a network-forming component, and when it is contained in an amount of more than 0%, it promotes stable glass formation while increasing the chemical durability of the glass. Therefore, the lower limit of the content of the SiO2 component is preferably more than 0%, more preferably 1.0% or more, even more preferably 1.5% or more, even more preferably 2.0% or more, even more preferably 5.0% or more, and most preferably 10.0% or more. On the other hand, if the content of the SiO2 component is large, the refractive index decreases and the glass transition point increases, so the upper limit is preferably 30.0% or less, more preferably 28.0% or less, even more preferably 25.0% or less, even more preferably 23.0% or less, and most preferably 20.0% or less.

[0021] The B2O3 component is a network-forming component that can promote the formation of stable glass in the optical glass of the present invention that contains a large amount of rare earth oxides, and is a component that can increase the devitrification resistance of the glass, increase the Abbe number, and lower the glass transition point. Therefore, the lower limit of the content of the B2O3 component is preferably 10.0% or more, more preferably 12.0% or more, even more preferably 13.0% or more, even more preferably 15.0% or more, and most preferably 16.0% or more. On the other hand, if the content of the B2O3 component is high, the refractive index decreases and the chemical durability of the glass decreases. Therefore, the upper limit is preferably 30.0% or less, more preferably 28.0% or less, even more preferably 25.0% or less, even more preferably 24.0% or less, even more preferably 23.0% or less, and most preferably 22.0% or less.

[0022] When the Al2O3 component is contained at more than 0%, it promotes stable glass formation while increasing the viscosity during glass melting and enhancing the chemical durability of the glass. Therefore, the lower limit of the content of the Al2O3 component is preferably more than 0%, more preferably 1.0% or more, even more preferably 1.5% or more, even more preferably 2.0% or more, and most preferably 3.0% or more, but may be 0%. On the other hand, if the content of the Al2O3 component is high, the devitrification resistance of the glass deteriorates, so the upper limit of the content of the Al2O3 component is preferably 20.0% or less, more preferably 15.0% or less, even more preferably 13.0% or less, still more preferably 10.0% or less, and most preferably 9.0% or less.

[0023] The Y2O3 component is a component that increases the refractive index of the glass, increases the Abbe number, and improves chemical durability. Therefore, the content of the Y2O3 component is preferably more than 0%, more preferably 2.0% or more, even more preferably 3.0% or more, and most preferably 5.0% or more, but may be 0%. On the other hand, a high content of the Y2O3 component impairs the stability of the glass and deteriorates the devitrification resistance, so the upper limit of the Y2O3 content is preferably 30.0% or less, more preferably 28.0% or less, even more preferably 25.0% or less, and most preferably 20.0% or less.

[0024] The La2O3 component is a component that can increase the refractive index, increase the Abbe number, and improve chemical durability. Therefore, the content of the La2O3 component is preferably 15.0% or more, more preferably 18.0% or more, even more preferably 19.0% or more, and most preferably 20.0% or more. On the other hand, if the content of the La2O3 component is high, the specific gravity increases and the glass transition point becomes high. Therefore, the content of the La2O3 component is preferably set to 45.0% or less, more preferably 40.0% or less, even more preferably 38.0% or less, and most preferably 35.0% or less.

[0025] The Gd2O3 component is a component that increases the refractive index of glass, and is a component that improves chemical durability (particularly acid resistance) when contained in place of the RO component (wherein R is one or more selected from Mg, Ca, Sr, and Ba). Therefore, the lower limit of the content of the Gd2O3 component is preferably more than 0%, more preferably 0.6% or more, even more preferably 0.8% or more, and most preferably 1.0% or more. On the other hand, a high content of the Gd2O3 component leads to an increase in specific gravity, which leads to an increase in the cost of the glass. Therefore, the upper limit of the content of the Gd2O3 component is preferably 20.0% or less, more preferably 15.0% or less, even more preferably 10.0% or less, and most preferably 8.0% or less.

[0026] The upper limit of the Yb2O3 component content is preferably 10.0% or less, more preferably 8.0% or less, even more preferably 5.0% or less, still more preferably 3.0% or less, and most preferably 1.0% or less.

[0027] The TiO2 component is a component that can increase the refractive index of the glass and improve the devitrification resistance. Therefore, the lower limit of the content of the TiO2 component is preferably more than 0%, more preferably 0.01% or more, even more preferably 0.02% or more, and most preferably 0.03% or more, but may be 0%. On the other hand, when the TiO2 component is contained in excess, it causes coloration of the glass and reduces the Abbe number. Therefore, the upper limit of the TiO2 component content is preferably 12.0% or less, more preferably 10.0% or less, even more preferably 8.0% or less, and most preferably 5.0% or less.

[0028] The ZrO2 component is a component that can increase the refractive index and chemical durability. Therefore, the content of the ZrO2 component is preferably more than 0%, more preferably 0.50% or more, even more preferably 0.80% or more, and most preferably 1.0% or more, but may be 0%. On the other hand, if the ZrO2 component is contained in excess, the Abbe number will be small and the devitrification resistance will be reduced, so the upper limit of the content of the ZrO2 component is preferably 10.0% or less, more preferably 9.0% or less, even more preferably 8.0% or less, and most preferably 5.0% or less.

[0029] The Nb2O5 component is a component that can increase the refractive index of glass, but it also reduces the Abbe number and devitrification resistance, leading to an increase in the cost of the glass. Therefore, the upper limit of the content of the Nb2O5 component is preferably 10.0% or less, more preferably 8.0% or less, even more preferably 5.0% or less, even more preferably 3.0% or less, and even more preferably 2.0% or less. In particular, from the viewpoint of reducing material costs, it is most preferable that the Nb2O5 component is not contained.

[0030] The Ta2O5 component is a component that can increase the refractive index of glass, but also leads to an increase in the cost of glass. Therefore, the content of the Ta2O5 component is preferably 10.0% or less, more preferably 8.0% or less, even more preferably 5.0% or less, even more preferably 3.0% or less, and even more preferably 2.0% or less as the upper limit. In particular, from the viewpoint of reducing material costs, it is most preferable that the Ta2O5 component is not contained.

[0031] When the WO3 component is contained at more than 0%, it is a component that can increase the refractive index and lower the glass transition point, but if the content is high, it is a component that leads to an increase in specific gravity and glass cost. Therefore, the content of the WO3 component is preferably 10.0% or less, more preferably 8.0% or less, even more preferably 5.0% or less, even more preferably 3.0% or less, and even more preferably 2.0% or less as the upper limit. In particular, from the viewpoint of reducing material costs, it is most preferable that the WO3 component is not contained.

[0032] When the Bi2O3 component is contained at more than 0%, it is a component that can increase the refractive index and lower the glass transition point, but if the content is high, it is a component that leads to an increase in specific gravity and glass cost. Therefore, the content of the Bi2O3 component is preferably 10.0% or less, more preferably 8.0% or less, even more preferably 5.0% or less, even more preferably 3.0% or less, and even more preferably 2.0% or less. In particular, from the viewpoint of reducing material costs, it is most preferable that the Bi2O3 component is not contained.

[0033] The ZnO component is a component that can lower the glass transition point and improve devitrification resistance when contained at more than 0%. In addition, compared with the Li2O component that can be expected to have the same effects, the ZnO component is more effective in improving devitrification resistance in the mold press molding process and in improving chemical durability. Therefore, the lower limit of the content of the ZnO component is preferably 1.0% or more, more preferably 2.0% or more, even more preferably 3.0% or more, and most preferably 4.0% or more. On the other hand, if the content of the ZnO component is high, the refractive index decreases and the devitrification resistance decreases, so the upper limit of the content of the ZnO component is preferably 20.0% or less, more preferably 18.0% or less, even more preferably 16.0% or less, still more preferably 15.0% or less, and most preferably 14.0% or less.

[0034] When the RO component (wherein R is one or more selected from Mg, Ca, Sr, and Ba) is contained at more than 0%, it has the effect of increasing the refractive index without decreasing the Abbe number. Therefore, the lower limit of the mass sum of the RO component content is preferably 0.1% or more, more preferably 0.5% or more, even more preferably 0.6% or more, and most preferably 1.0% or more, but it may be 0%. On the other hand, if the sum of the RO components is too large, it leads to a decrease in chemical durability and devitrification resistance, and therefore the upper limit of the sum of the RO components is preferably 20.0% or less, more preferably 10.0% or less, even more preferably 8.0% or less, and most preferably 6.0% or less.

[0035] Among RO (wherein R is one or more selected from Mg, Ca, Sr, and Ba) components, the MgO component increases the refractive index without decreasing the Abbe number, but is a component that is relatively likely to decrease chemical durability (particularly acid resistance). Therefore, the upper limit of the content of the MgO component is preferably 10.0% or less, more preferably 8.0% or less, even more preferably 6.0% or less, and most preferably 5.0% or less, but may be 0%.

[0036] Among RO (wherein R is one or more selected from Mg, Ca, Sr, and Ba) components, the CaO component is a component that increases the refractive index without decreasing the Abbe number, while relatively preventing a decrease in chemical durability (particularly acid resistance). Therefore, the lower limit of the CaO component content is preferably more than 0%, more preferably 0.5% or more, even more preferably 1.0% or more, and most preferably 1.5% or more, but may be 0%. On the other hand, a high CaO content reduces devitrification resistance and deteriorates chemical durability (particularly acid resistance), so the upper limit of the CaO content is preferably 20.0% or less, more preferably 15.0% or less, even more preferably 10.0% or less, still more preferably 8.0% or less, and most preferably 5.0% or less.

[0037] Among RO (wherein R is one or more selected from Mg, Ca, Sr, and Ba) components, the SrO component increases the refractive index without decreasing the Abbe number, but is relatively prone to decrease the chemical durability (particularly acid resistance) and increase the specific gravity. Therefore, the upper limit of the content of the SrO component is preferably 5.0% or less, more preferably 4.0% or less, even more preferably 3.0% or less, and most preferably 2.0% or less, but may be 0%.

[0038] Among RO (wherein R is one or more selected from Mg, Ca, Sr, and Ba) components, the BaO component is a component that increases the specific gravity and leads to a decrease in chemical durability (particularly acid resistance). Therefore, the upper limit of the content of the BaO component is preferably 5.0% or less, more preferably 4.0% or less, even more preferably 3.0% or less, and most preferably 2.0% or less, but may be 0%.

[0039] The Rn2O (wherein Rn is one or more selected from Li, Na, and K) component lowers the melting temperature of the glass, thereby contributing to a reduction in the cost of producing the glass, and lowers the glass transition point. Therefore, the lower limit of the mass sum of the R2O component content is preferably more than 0%, more preferably 1.0% or more, even more preferably 2.0% or more, and most preferably 3.0% or more, but may be 0%. On the other hand, if the sum of the contents of the Rn2O components is too large, it leads to a decrease in chemical durability and devitrification resistance. Therefore, the upper limit of the sum of the contents of the Rn2O components is preferably 15.0% or less, more preferably 12.0% or less, even more preferably 10.0% or less, and most preferably 7.0% or less.

[0040] The Li2O component has the lightest specific gravity among Rn2O (wherein Rn is one or more selected from Li, Na, and K) components, is highly effective in lowering the glass transition point, and is a component that is less likely to worsen devitrification. Therefore, the lower limit of the content of the Li2O component is preferably more than 0%, more preferably 1.0% or more, even more preferably 2.0% or more, even more preferably 2.5% or more, and most preferably 3.0% or more, but may be 0%. On the other hand, if the content of the Li2O component is high, chemical durability is reduced, leading to a decrease in devitrification resistance not only during glass production but also during the mold press forming process. Therefore, the upper limit is preferably 10.0% or less, more preferably 8.0% or less, even more preferably 6.0% or less, and most preferably 5.5% or less.

[0041] The K2O component is a component that, when contained in excess, reduces chemical durability and devitrification resistance, and therefore the upper limit is preferably 8.0% or less, more preferably 5.0% or less, further preferably 3.0% or less, and most preferably 2.0% or less, but may be 0%.

[0042] The Na2O component is a component that, when contained in excess, reduces chemical durability and devitrification resistance, and therefore the upper limit is preferably 8.0% or less, more preferably 5.0% or less, further preferably 3.0% or less, and most preferably 2.0% or less, but may be 0%.

[0043] The upper limit of the content of the P2O5 component is preferably 5.0% or less, more preferably 3.0% or less, more preferably 1.0% or less, and even more preferably 0.5% or less, but may be 0%.

[0044] The upper limit of the F content is preferably 5.0% or less, more preferably 3.0% or less, more preferably 1.0% or less, further preferably 0.5% or less, and further preferably 0.3% or less, but may be 0%.

[0045] The upper limit of the content of the TeO2 component is preferably 3.0% or less, more preferably 2.0% or less, more preferably 1.0% or less, and even more preferably 0.5% or less, but may be 0%.

[0046] The upper limit of the Ga2O3 component content is preferably 3.0% or less, more preferably 2.0% or less, more preferably 1.0% or less, and even more preferably 0.5% or less, but may be 0%.

[0047] The upper limit of the GeO2 component content is preferably 3.0% or less, more preferably 2.0% or less, more preferably 1.0% or less, and even more preferably 0.5% or less, but may be 0%.

[0048] The upper limit of the CeO2 content is preferably 3.0% or less, more preferably 2.0% or less, more preferably 1.0% or less, and further preferably 0.5% or less, but may be 0%.

[0049] The content of Er2O3 component and Pr2O3 component is preferably 1.0% or less, more preferably 0.5% or less, more preferably 0.1% or less, and most preferably substantially none is contained.

[0050] The upper limit of the content of the SnO2 component is preferably 2.0% or less, more preferably 1.0% or less, and further preferably 0.5% or less, but may be 0%.

[0051] The Sb2O3 component is a component that promotes clarification and defoaming when melting the glass. Therefore, the lower limit of the Sb2O3 component is preferably more than 0%, more preferably 0.005% or more, even more preferably 0.01% or more, and most preferably 0.015% or more, but may be 0%. On the other hand, if the content of Sb2O3 is high, the transmittance of visible light in the short wavelength region is deteriorated, and excessive foaming occurs during glass melting, leading to bubble defects. Therefore, the upper limit of the content of Sb2O3 is preferably 0.2% or less, more preferably 0.15% or less, and even more preferably 0.1% or less.

[0052] The component for clarifying and defoaming the glass is not limited to the above Sb2O3 component, and any fining agent, defoaming agent or combination thereof known in the field of glass manufacturing can be used.

[0053] The mass sum of the Ln2O3 component (wherein Ln is one or more selected from Y, La, Gd, and Yb) content can increase the refractive index of the glass, but if it is contained in excess, it increases the devitrification tendency of the glass. Therefore, the lower limit of the sum of the Ln2O3 component content is preferably 20.0% or more, more preferably 25.0% or more, and even more preferably 30.0% or more. On the other hand, the upper limit of the sum of the Ln2O3 component content is preferably 55.0% or less, more preferably 50.0% or less, even more preferably 48.0% or less, and most preferably 45.0% or less.

[0054] When the mass sum of the Li2O component and the ZnO component (Li2O+ZnO) exceeds 0%, the glass transition point can be lowered. Therefore, the lower limit of the mass sum (Li2O+ZnO) is preferably 2.0% or more, more preferably 4.0% or more, even more preferably 8.0% or more, and most preferably 10.0% or more. On the other hand, if the content of the sum by mass (Li2O+ZnO) is high, the chemical durability and devitrification resistance of the glass are reduced. Therefore, the upper limit of the sum by mass (Li2O+ZnO) is preferably 25.0% or less, more preferably 23.0% or less, even more preferably 20.0% or less, and most preferably 19.0% or less.

[0055] The chemical durability (particularly acid resistance) of glass can be improved by appropriately adjusting the mass ratio Al2O3 / B2O3 of the Al2O3 component to the B2O3 component to a value greater than 0. In the present invention, it has been discovered that when the mass ratio Al2O3 / B2O3 is x, the weight loss rate y (mass%) of a glass sample measured in accordance with the Japan Optical Glass Industry Association standard (JOGIS06-2019 Measurement method for chemical durability of optical glass) can be predicted by the following formula (1). y=-0.5411×x+0.7383 (1) Therefore, the lower limit of the mass ratio Al2O3 / B2O3 is preferably 0.05 or more, more preferably 0.1 or more, even more preferably 0.15 or more, and most preferably 0.163 or more. On the other hand, if the mass ratio Al2O3 / B2O3 is too large, it will result in a decrease in devitrification resistance, so the upper limit of the mass ratio Al2O3 / B2O3 is preferably 2.0 or less, more preferably 1.2 or less, even more preferably 1.0 or less, even more preferably 0.8 or less, and most preferably 0.5 or less.

[0056] The chemical durability (particularly acid resistance) of the glass can be increased when the mass ratio SiO2 / B2O3 of the SiO2 component to the B2O3 component exceeds 0. Therefore, the lower limit of the mass ratio SiO2 / B2O3 is preferably 0.2 or more, more preferably 0.4 or more, even more preferably 0.7 or more, and most preferably 0.75 or more. On the other hand, if the mass ratio SiO2 / B2O3 is too large, the glass transition point increases, so the upper limit of the mass ratio SiO2 / B2O3 is preferably 4.0 or less, more preferably 2.0 or less, even more preferably 1.5 or less, and most preferably 1.2 or less.

[0057] The chemical durability (particularly acid resistance) of the glass can be improved by appropriately adjusting the ratio (SiO2+Al2O3) / B2O3, which is the mass sum of the SiO2 and Al2O3 components relative to the B2O3 component, to a value greater than 0. Therefore, the lower limit of (SiO2+Al2O3) / B2O3 is preferably 0.3 or more, more preferably 0.5 or more, even more preferably 0.7 or more, and most preferably 0.9 or more. On the other hand, if (SiO2+Al2O3) / B2O3 is too large, the glass transition point increases, so the upper limit of (SiO2+Al2O3) / B2O3 is preferably 5.0 or less, more preferably 3.0 or less, even more preferably 2.0 or less, and most preferably 1.5 or less.

[0058] The chemical durability (particularly acid resistance) of the glass can be increased by appropriately adjusting the mass sum of the SiO2 component and the Al2O3 component contents (SiO2+Al2O3) to be greater than 0. Therefore, the lower limit of (SiO2+Al2O3) is preferably 10.0 or more, more preferably 14.0 or more, even more preferably 16.0 or more, and most preferably 19.0 or more. On the other hand, if (SiO2+Al2O3) is too large, the glass transition point increases, so the upper limit of (SiO2+Al2O3) is preferably 35.0 or less, more preferably 30.0 or less, even more preferably 28.0 or less, and most preferably 27.0 or less.

[0059] [Ingredients that should not be included] Next, components that should not be contained in the optical glass of the present invention and components whose inclusion is undesirable will be described.

[0060] Other components may be added as necessary within the range that does not impair the characteristics of the glass of the present invention. However, each transition metal component, such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag, and Mo, except for Ti, Zr, Nb, W, La, Gd, Y, Yb, and Lu, has the property that the glass is colored and absorbs specific wavelengths in the visible range even when contained alone or in combination in small amounts, so it is preferable that it is not substantially contained, especially in optical glasses that use wavelengths in the visible range. Also, it is preferable that each component, Rb and Cs, is not contained from the viewpoint of suppressing coloration of the glass.

[0061] Furthermore, since lead compounds such as PbO and arsenic compounds such as As2O3 are components that have a high environmental impact, it is desirable that they are not contained substantially, that is, that they are not contained at all except for unavoidable contamination.

[0062] Furthermore, in recent years, there has been a trend to refrain from using the components Th, Cd, Tl, Os, Be, and Se as harmful chemical substances, and environmental measures are required not only in the glass manufacturing process but also in the processing process and disposal after commercialization. Therefore, when environmental impact is important, it is preferable that these components are not substantially contained.

[0063] [Physical Properties] The refractive index (n d ) is preferably 1.60000 or more, more preferably 1.63000 or more, even more preferably 1.66000 or more, and most preferably 1.67000 or more. d ) is preferably up to 1.76000, more preferably up to 1.73000, even more preferably up to 1.72000, and most preferably up to 1.70000. Here, in the present invention, the refractive index (n d ) is shown as a measured value for the d-line (587.56 nm) of a helium lamp in accordance with the V-block method specified in JIS B7071-2.

[0064] The Abbe number (ν d ) is preferably 45.00 or more, more preferably 47.00 or more, even more preferably 50.00 or more, and most preferably 51.00 or more. d ) is preferably 60.00 or less, more preferably 58.00 or less, even more preferably 55.00 or less, and most preferably 54.00 or less. Here, in the present invention, the Abbe number (ν d ) is calculated based on the V-block method specified in JIS B7071-2 by dividing the refractive index of the d line and the refractive index of the F line (486.13 nm) of a hydrogen lamp (n F ), and the refractive index for the C line (656.27 nm) (n C ) value, the Abbe number (ν d )=[(n d -1) / (n F -n C)] was calculated using the formula:

[0065] The glass of the present invention preferably has a glass transition point of 600°C or less. This allows the glass to soften at a lower temperature, and therefore allows the glass to be molded by press molding at a lower temperature. In addition, oxidation of the mold used in mold press molding can be reduced, thereby extending the life of the mold. Therefore, the upper limit of the glass transition point of the optical glass of the present invention is preferably 600°C, more preferably 580°C, even more preferably 570°C, and most preferably 550°C. The lower limit of the glass transition point of the optical glass of the present invention is not particularly limited, but is preferably 400°C, more preferably 450°C, and even more preferably 500°C. Here, in the present invention, the glass transition points of the glasses in the examples and comparative examples were determined from thermal expansion curves obtained by measuring the relationship between temperature and elongation of a sample in accordance with the Japan Optical Glass Industry Association standard (JOGIS08-2019 Measurement method for thermal expansion of optical glass).

[0066] The upper limit of the acid resistance (RA) of the glass of the present invention is preferably not more than Class 5, more preferably not more than Class 4, and even more preferably not more than Class 3, but the lower limit may be preferably not less than Class 2, and more preferably not less than Class 1. This enables the glass to satisfy the strict safety standards required for automobiles and to be used in optical elements mounted on automobiles. Here, in the present invention, the acid resistance of the glass of the examples and comparative examples was measured in accordance with the Japan Optical Glass Industry Association standard (JOGIS06-2019 Measuring method for chemical durability of optical glass). That is, a glass sample crushed to a particle size of 425 to 600 μm was placed in a pycnometer and placed in a platinum cage. The platinum cage was placed in a quartz glass round-bottom flask containing a 0.01N nitric acid aqueous solution and treated in a boiling water bath for 60 minutes. The weight loss rate (mass%) of the glass sample after the treatment was calculated, and the weight loss rate (mass%) of less than 0.20 was classified as Class 1, the weight loss rate of less than 0.20 to 0.35 was classified as Class 2, the weight loss rate of less than 0.35 to 0.65 was classified as Class 3, the weight loss rate of less than 0.65 to 1.20 was classified as Class 4, the weight loss rate of less than 1.20 to 2.20 was classified as Class 5, and the weight loss rate of 2.20 or more was classified as Class 6. In this case, the smaller the class number, the better the acid resistance of the glass.

[0067] [Preforms and optical elements] From the produced optical glass, a glass molded body can be produced, for example, by using a polishing means or a mold press molding means such as reheat press molding or precision press molding. That is, a glass molded body can be produced by performing mechanical processing such as grinding and polishing on the optical glass, a preform for mold press molding can be produced from the optical glass, and the preform can be subjected to reheat press molding and then polished to produce a glass molded body, or a preform produced by polishing or a preform molded by known floating molding can be subjected to precision press molding to produce a glass molded body. Note that the means for producing a glass molded body are not limited to these means.

[0068] Thus, the optical glass of the present invention is useful for various optical elements and optical designs. In particular, it is preferable to form a preform from the optical glass of the present invention and use the preform to perform reheat press molding, precision press molding, or the like to produce optical elements such as lenses and prisms. This makes it possible to form a preform with a large diameter, so that while the optical element can be made larger, high-definition and high-precision imaging and projection characteristics can be achieved when used in optical equipment.

[0069] The glass molded article made of the optical glass of the present invention can be used for optical elements such as lenses, prisms, mirrors, etc., and can be adapted to low-cost mass production of lenses by precision mold press molding. Since the glass molded article satisfies the strict safety standards for automobiles, it can realize high performance optical devices to be installed in automobiles.

[0070] The upper limit of the specific gravity (d) of the optical glass of the present invention is preferably 4.50 or less, more preferably 4.00 or less, and most preferably 3.80 or less. By reducing the specific gravity, the glass becomes lighter, making it possible to reduce the weight of optical devices. Here, in the present invention, the specific gravity of the glasses in the examples and comparative examples was measured in accordance with the Japan Optical Glass Industry Association standard (JOGIS05-2019 Method for measuring the specific gravity of optical glass).

[0071] The transmittance of the glass of the present invention is preferably λ 70 = 370 nm or less, more preferably λ 70 = 360 nm or less, most preferably λ 70 The upper limit is preferably λ5=330 nm or less, more preferably λ5=320 nm or less, and most preferably λ5=310 nm or less. 70 By shortening the wavelength of λ or λ5, the glass can be made to have a high transmittance in the visible light range, thereby enabling high performance optical devices. Here, in the present invention, the transmittance of the glass in the examples and comparative examples was measured in accordance with the Japan Optical Glass Industry Association standard (JOGIS02-2019 Method for measuring the degree of coloration of optical glass). In the present invention, the presence and degree of coloration of the glass was determined by measuring the transmittance of the glass. Specifically, the spectral transmittance of a 10±0.1 mm thick parallel polished product was measured in accordance with JISZ8722 from 200 to 700 nm, and λ 70 (wavelength when transmittance is 70%) and λ5 (wavelength when transmittance is 5%) were calculated.

[0072] [Manufacturing method] For the glasses of the Examples and Comparative Examples, high-purity raw materials used in ordinary optical glass, such as the corresponding oxides, hydroxides, carbonates, nitrates, fluorides, and metaphosphate compounds, were selected as the raw materials for each component, and were weighed out and mixed uniformly to obtain the composition ratios of each Example and Comparative Example shown in the table. The mixture was then placed in a quartz crucible or a platinum crucible and melted in an electric furnace at a temperature range of 1100 to 1400°C for 1 to 5 hours depending on the melting difficulty of the glass composition. The mixture was then stirred and homogenized, and bubble-removal was performed, after which the temperature was lowered to 1000 to 1300°C and stirred and homogenized, before being poured into a mold and slowly cooled to produce the glass.

[0073] [Glass molding] The glass of the present invention can be melt-molded by a known method. However, the means for shaping the glass melt is not limited.

[0074] [Optical elements] A glass molded body can be produced from the produced optical glass by, for example, polishing means or mold press molding means such as reheat press molding or precision press molding. That is, a glass molded body can be produced by subjecting the optical glass to mechanical processing such as grinding and polishing. The means for producing the glass molded body are not limited to these means. EXAMPLES

[0075] The compositions of the examples and comparative examples of the glass of the present invention and the refractive index (n d ), Abbe number (ν d ), acid resistance (RA), predicted weight loss rate of glass sample, glass transition temperature (Tg), specific gravity (d), transmittance (λ 70 , λ5) are shown in Tables 1 to 3.

[0076] The optical glass of the present invention is produced by selecting high-purity raw materials used in ordinary optical glass, such as the corresponding oxides, hydroxides, carbonates, nitrates, sulfates, fluorides, and metaphosphate compounds, as the raw materials for each component, weighing them out so as to obtain the composition ratios of each example shown in the table, mixing them uniformly, and then placing them in a platinum crucible. Depending on the degree of difficulty in melting the glass raw materials, the mixture is melted in an electric furnace at a temperature range of 1100 to 1500°C for 30 minutes to 2 hours. The mixture is then stirred and homogenized, and poured into a mold or the like, and slowly cooled. In the manufacture of the optical glass of the present invention, particular attention should be paid to the weighing and mixing of the raw materials. By using compounds, particularly LiCO3, with uniform particle size, the effect of the Li2O component of the optical glass of the present invention is more effectively exhibited. The particle size is approximately 10 to 30 μm on average. Therefore, in order to uniformly mix the raw materials including these raw materials, a mixing and stirring device and stirring auxiliary equipment are used, and the raw material mixing process lasts for 1 minute.

[0077] [Table 1]

[0078] [Table 2]

[0079] [Table 3]

[0080] As shown in the table, the glasses of the examples of the present invention all have a refractive index (n d ) was greater than or equal to 1.65000 and less than or equal to 1.75000, which was within the desired range.

[0081] In addition, the glasses in the examples of the present invention all have an Abbe number (ν d ) is 45.00 or more, more specifically 48.00 or more, and this Abbe number (ν d) was less than or equal to 60.00, more specifically less than or equal to 57.00, which was within the desired range.

[0082] It was clear that the glasses of the examples of the present invention had chemical durability (acid resistance) class 3 or higher according to the powder method, and thus met the strict safety standards for automobiles. On the other hand, Comparative Example 1, which does not satisfy the scope of the claims, could not be said to have a sufficient value for the class of chemical durability (acid resistance).

[0083] The glasses in the examples of the present invention all had a glass transition point (Tg) of 600° C. or less, more specifically 560° C. or less, which was within the desired range.

[0084] The glasses of the examples of the present invention were all highly stable glasses.

[0085] Therefore, it was made clear that the optical glasses of the Examples of the present invention are optical glasses that have high optical constants of high refractive index and low dispersion, while also having high chemical durability and allowing precision molding.

[0086] Although the present invention has been described in detail for purposes of illustration, it will be understood that the present embodiments are for illustrative purposes only and that numerous modifications may be made by those skilled in the art without departing from the spirit and scope of the invention.

Claims

1. In mass% based on oxide, The sum of the content of the components (Li 2 O + ZnO) is 6.0% or more, Mass ratio of component contents Al 2 O 3 / B 2 O 3 is greater than 0 and less than 2.5 SiO 2 / B 2 O 3 is 0.6 or more, (SiO 2 +Al 2 O 3 ) / B 2 O 3 is 0.8 or more, Refractive index (n d ) Optical glass with a powder method acid resistance rating (RA) of grade 3 or higher.

2. Mass ratio of component contents Al 2 O 3 / B 2 O 3 The optical glass according to claim 1 , wherein the refractive index is 1.5 or less.

3. Abbe number (ν d 3. The optical glass according to claim 1, having a molecular weight of 45 or more and a glass transition point (Tg) of 560° C. or less.

4. Ratio of component contents Al 2 O 3 / B 2 O 3 The powder method acid resistance evaluation result was 0.65>-0.5411×(Al 2 O 3 / B 2 O 3 3. The optical glass according to claim 1, wherein

5. The sum of the contents of the components (SiO 2 +Al 2 O 3 3. The optical glass according to claim 1, wherein the .lambda.

6. An optical element comprising the optical glass according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • JP137701A

  • Optical glass, preform material, and optical element

    WO2018003720A1